Hubungan Antara Guru dan Orang Tua Melalui Program Parenting di TK Taruna Asih - Rifka Ainunida; Ine Apriani; Santi Nurandiyani; Nadia Nurjanah (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2024)
The aim of this research is to find out how the relationship between teachers and parents is through the parenting program at Taruna Asih Kindergarten. This research method is a qualitative method. This research involved 23 parents and 3 teachers at school. Data collection techniques were carried out through observation, interviews and documentation studies. The research results found that the relationship between teachers and parents must be balanced, because care at school and home is very useful in monitoring children's growth and development. The parenting program given to parents at Taruna Asih Kindergarten has been proven to influence parents' parenting patterns towards children. Parenting patterns are behaviors that parents apply to children and are relatively consistent from time to time.